2007
DOI: 10.1007/s10545-007-0487-0
|View full text |Cite
|
Sign up to set email alerts
|

l‐2‐Hydroxyglutaric aciduria, a defect of metabolite repair

Abstract: L-2-hydroxyglutaric aciduria is a metabolic disorder in which L-2-hydroxyglutarate accumulates as a result of a deficiency in FAD-linked L-2-hydroxyglutarate dehydrogenase, a mitochondrial enzyme converting L-2-hydroxyglutarate to alpha-ketoglutarate. The origin of the L-2-hydroxyglutarate, which accumulates in this disorder, is presently unknown. The oxidation-reduction potential of the 2-hydroxyglutarate/alpha-ketoglutarate couple is such that L-2-hydroxyglutarate could potentially be produced through the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
131
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 41 publications
3
131
1
Order By: Relevance
“…The findings presented here substantiate prior genetic evidence implicating LDH and MDH as cellular sources of L-2HG 1618,21 . In hypoxia, cells selectively produce L-2HG in a manner primarily dependent on LDHA and MDH2 17,18 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings presented here substantiate prior genetic evidence implicating LDH and MDH as cellular sources of L-2HG 1618,21 . In hypoxia, cells selectively produce L-2HG in a manner primarily dependent on LDHA and MDH2 17,18 .…”
Section: Discussionsupporting
confidence: 88%
“…3b–f). Collectively, these findings substantiate genetic evidence suggesting that LDH and MDH enzymes contribute to cellular production of L-2HG 1618,21 .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Finally, there is evidence that wildtype IDH1 and IDH2 also slowly form D-2HG from ␣-ketoglutarate (15). A known source of L-2HG in mammalian cells is a low side activity of malate dehydrogenase, converting ␣-ketoglutarate to L-2HG at the expense of NADH (16,17). Such an L-2HG-producing side activity has also been demonstrated for the mitochondrial malate dehydrogenases of Arabidopsis thaliana (18).…”
mentioning
confidence: 87%
“…It is now known that the mutated gene in L-2-HGA affects subject maps at chromosome 14q22 2,3 and encodes a FAD-dependent enzyme 2 known as L-2-hydroxyglutaric acid dehydrogenase. 2,4,5 Once clarified the molecular basis involved in L-2-HGA, the reports of co-segregating mutations started to increase and are now available for several populations. At the time of this study, 32 distinct mutations found in a total of 50 affected families are known from several distinct populations.…”
mentioning
confidence: 99%